2017
DOI: 10.3390/rs9070714
|View full text |Cite
|
Sign up to set email alerts
|

First Assessment of Sentinel-1A Data for Surface Soil Moisture Estimations Using a Coupled Water Cloud Model and Advanced Integral Equation Model over the Tibetan Plateau

Abstract: Abstract:The spatiotemporal distribution of soil moisture over the Tibetan Plateau is important for understanding the regional water cycle and climate change. In this paper, the surface soil moisture in the northeastern Tibetan Plateau is estimated from time-series VV-polarized Sentinel-1A observations by coupling the water cloud model (WCM) and the advanced integral equation model (AIEM). The vegetation indicator in the WCM is represented by the leaf area index (LAI), which is smoothed and interpolated from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 66 publications
(116 reference statements)
1
59
0
Order By: Relevance
“…This result was expected due to the nature of the study site, which is characterized by low value of surface roughness [22,67]. This is in accordance with several previous studies which have found that, for agricultural surfaces, the exponential function provides the best match between predicted and SAR backscatters [82][83][84][85]. Generally speaking, in spite of the slight underestimation, one can state that the simulations of IEM by using the measured L are very satisfying with respect to what have been reported in previous works [20,67,80,81,86].…”
Section: Evaluation Of the Oh And Iem Modelssupporting
confidence: 91%
“…This result was expected due to the nature of the study site, which is characterized by low value of surface roughness [22,67]. This is in accordance with several previous studies which have found that, for agricultural surfaces, the exponential function provides the best match between predicted and SAR backscatters [82][83][84][85]. Generally speaking, in spite of the slight underestimation, one can state that the simulations of IEM by using the measured L are very satisfying with respect to what have been reported in previous works [20,67,80,81,86].…”
Section: Evaluation Of the Oh And Iem Modelssupporting
confidence: 91%
“…The calibration of empirical model parameters is typically achieved by fitting a sample of satellite observations and ground measurements (for example, by minimising a cost function as described by Bai et al (2017)). When analytical model inversion is not possible, it is common to use look up tables or machine learning approaches.…”
Section: Methods For Soil Moisture Retrieval From Sarmentioning
confidence: 99%
“…e above-mentioned models are commonly applied to bare soil and cannot be applied directly in vegetation cover areas, due to the multiple scattering effects of vegetation canopies [14]. e water cloud model (WCM), a semiempirical forward model, generally assumes that the vegetation canopy is a uniform layer of a cloud of water droplets and has been widely used to separate out the contribution of vegetation backscatter [15][16][17][18]. To minimize the effects of vegetation, many researchers have attempted to utilize optical remote sensing to obtain additional vegetation information [19][20][21].…”
Section: Introductionmentioning
confidence: 99%